2023
DOI: 10.4103/aja2022126
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of exosomes in the development of testicular

Abstract: The mechanisms of testicular development in mammals are complex. Testis is an organ that produces sperm and secretes androgens. It is rich in exosomes and cytokines that mediate signal transduction between tubule germ cells and distal cells, promoting testicular development and spermatogenesis. Exosomes are nanoscale extracellular vesicles that transmit information between cells. By transmitting information, exosomes play an important role in male infertility diseases such as azoospermia, varicocele, and testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Characterization and analysis of the MSC secretome might help to elucidate the precise role of MSCs in tissue regeneration. For example, it has been demonstrated that MSCs release exosomes containing different RNA molecules, such as miRNAs and proteins, that may be key mediators of this process [ 130 , 131 ]. According to a recent study, MSC treatment mitigated busulfan-induced azoospermia in rats by altering the expression of spermatogenesis-related miRNAs and their target genes [ 132 ].…”
Section: Mirnas In Fertility Preservation Strategiesmentioning
confidence: 99%
“…Characterization and analysis of the MSC secretome might help to elucidate the precise role of MSCs in tissue regeneration. For example, it has been demonstrated that MSCs release exosomes containing different RNA molecules, such as miRNAs and proteins, that may be key mediators of this process [ 130 , 131 ]. According to a recent study, MSC treatment mitigated busulfan-induced azoospermia in rats by altering the expression of spermatogenesis-related miRNAs and their target genes [ 132 ].…”
Section: Mirnas In Fertility Preservation Strategiesmentioning
confidence: 99%